“Are They Getting Out of Control?”: The Renegotiation of Nursing Practice in the Maritimes, 1950-1970 - Twohig, Peter (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2015)
This article examines the renegotiation of nursing practice in the Maritime provinces in the mid-20th century. The rapidly growing number of nursing assistants in these years was both a response to the inadequate supply of registered nurses and the expansion of hospitals that characterized these years. Nursing assistants were a heterogeneous category of labour that had a long history within hospitals. But while it is readily acknowledged that nursing assistants have been important to nursing practice, there have been few analyses of nursing assistants. This study seeks to redress this imbalance and expand our collective understanding of the full spectrum of hospital-based labour.